(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The article studies the importance of strategic foresight in the management of textile corporations. The opinions of foreign scientists on the competitive position of enterprises, firms and companies are highlighted, the essence of the concepts of increasing the competitiveness of the enterprise in the industry, strategic thinking and strategic foresight are substantiated. At the same time, the concepts of strategic thinking as the ability to model the situation, reveal the need for change, develop a change strategy, use theoretical and practical methods and strategic analysis models developed in one’s managerial activities, and implement the strategy are substantiated. A model for the formation of strategic foresight of the competitive position of an enterprise in business is also developed.